Wcielenie w teologii Marcelego z Ancyry - Słomka, Jan (Vox Patrum, 2000)
Marcellus perceives the incarnation of Jesus as the moment when not only does the Logos assume a human body, but a change also occurs in God himself. The change consists in the expansion of a monad into a triad. It is the second transformation already. The first one took place at the beginning of creation. It was then that the Logos passed from the State of being „in God" to being „with God". Marcellus underlines that neither the first nor the latter can be defined as generation. The term „generation refers only to Jesus’ birth from Mary. The changes undergone by God, first at creation, then at the incarnation, are not of permanent nature. On the contrary, they are temporary and reversible. Upon completing the history of the world, God will return to the monadic State. The incarnation will also come to an end. Marcellus presents the incarnation as temporary and „external" in relation to the Logos. When the „carnal economy" is completed, the Logos is to return to His original State of resting „in God".